Preparation of Ga‐ZnO Nanoparticles Using Microwave and Ultrasonic Irradiation, and the Application of Poly(3, 4‐ethylenedioxythiophene)‐poly(styrenesulfonate) Hybrid Thermoelectric Films. Issue 22 (12th June 2019) - Hata, Shinichi; Taguchi, Kazuki; Oshima, Keisuke; Du, Yukou; Shiraishi, Yukihide; Toshima, Naoki
Abstract: The addition of inorganic materials with high thermoelectric properties is a popular approach to modulate the performance of Poly(3, 4‐ethylenedioxythiophene)‐poly(styrenesulfonate) (PEDOT‐PSS), but, the representative hybridization of PEDOT‐PSS and toxic Te or Bi is not practical considering safety. Here, we report a PEDOT‐PSS film including Ga‐ZnO (GZO) nanoparticles, which has higher reproducibility and thermoelectric properties. Interestingly, the PEDOT‐PSS film containing GZO nanoparticle of 1 atom% Ga exhibited a higher in‐plane thermoelectric power factor (38.4 μW m −1 K −2 ) than the pure PEDOT‐PSS (27.4 μW m −1 K −2 ), which is one of the highest values when compared to previous metallic oxide/PEDOT‐PSS or PEDOT system. The present results suggest a simple approach for electrical conductivity improvement of PEDOT‐PSS film: the Zn and Ga components are an efficient carrier promoter for improving the crystal growth and conformation of PEDOT. Abstract : Ga‐ZnO nanoparticles prepared using the microwave and ultrasonic irradiation enhance the organic thermoelectric properties of PEDOT‐PSS film by promoting the carrier flow. The Zn and Ga components in the film modified the crystallinity and the conformation of PEDOT, leading to an increase in electrical conductivity. This work suggests the evolution of hybrid‐type thermoelectric materials consisting of metal oxide and PEDOT‐PSS.